The utility of pre-procedural COVID-PCR testing for dental aerosol generating procedures is questionable - Syed Murtaza Raza Kazmi; Wafa Zehra Jamal; Khan, Farhan Raza (Journal of the Pakistan Medical Association, 2023)
Objectives: To compare the number of aerosol-generating procedures performed and the number of coronavirus disease-2019-positive workers in dental practice. Method: The audit study was conducted in May 2021 at the Aga Khan University Hospital, Karachi, and comprised data from April 1, 2020, to March 31, 2021, which was retrieved from dental clinics at the main hospital and its Clifton branch as well as in three secondary care hospitals in Garden, Kharadar, Karimabad areas of Karachi, and one in Hyderabad, Pakistan. Data of individuals who followed mandatory pre-procedural polymerase chain reaction testing in addition to using personal protective equipment in the main hospital and Clifton branch was placed in group A, and of those using personal protective equipment only at the 4 satellite clinics with no testing was placed in group B. Dental charts of patients who underwent dental aerosol-generating procedures were analysed. Number of dental clinics affected by coronavirus disease-2019 and number of dental patients who were reported positive on pre-procedural polymerase chain reaction testing were evaluated. Data was analysed using SPSS 23. Results: Of the 63 dental healthcare workers, 44(69.8%) were in group A and 19(30.2%) were in group B. In group A, 19(43.2%) were affected by coronavirus disease-2019 compared to 2(11%) in group B (p=0.01). Among 782(67.8%) patients who underwent polymerase chain reaction testing, 26(3.3%) turned out positive for coronavirus disease-2019. Due to the mandatory testing imposed on patients, 371/1153(32.2%) refused to get the desired dental treatment. Conclusion: The benefit of pre-procedural testing in dentistry remained uncertain.